Theoretical Research on the Pitting Damage Growth Characteristics under Stress - FU Yun-wei, GUO Bang, LI Zeng-guang, ZHANG Li-jun, XU Fei-ran (Cailiao Baohu, 2021)
Based on the law of pitting corrosion development speed and the accelerating effect of stress on corrosion current in the field coupon test, the differential equations of pitting corrosion speed and pit shape change law under stress were proposed and solved by numerical methods. Analysis results indicated that the stress could accelerated the pitting corrosion rate, the shape of pitting pits was affected by stress. Corrosion perpendicular to the principal stress axis was faster than others, pitting pits might gradually form flat pitting pits perpendicular to the principal stress, or even develop into cracks. Moreover, the stress could not have a significant effect on the corrosion rate until increased to a certain value. As for the hemispheric corrosive pits damage of 304 stainless steel, they would change to crack rapidly when the residual stress was greater than 180 MPa.